ANALYSIS OF PHRASE FUNCTIONS IN "DREAM" BY BABYMONSTER SONG LYRICS - Zahrotuhayaty, Ghafera Kamelia; Novari, Ari Fajria; Gumelar, Rizdki Elang (Journal of English Literature and Linguistic Studies, 2024)
This research is about analysis of phrase functions in "Dream" by Babymonster song lyrics using Nelson & Greenbaum theory. The goal of this research is to analyze the phrases functions found in Dream by Babymonster song lyrics. This research used a qualitative descriptive method. The primary data were the song lyrics, categorized into noun phrases, verb phrases, adjective phrases, adverb phrases, and prepositional phrases based on Nelson & Greenbaum's theory. The data analysis involved transcribing the lyrics, segmenting them into phrases, and determining their functions. The finding showed that noun phrases act as subjects, objects, and complements; verb phrases function as predicates; adjective phrases serve as complements and pre-modifiers; adverb phrases act as adverbials; and prepositional phrases function as post-modifiers and adverbials. This research provides insights into the syntactical structures and stylistic choices in "Dream."